Quantitative live cell imaging of a tauopathy model enables the identification of a polypharmacological drug candidate that restores physiological microtubule interaction - Pinzi, Luca; Conze, Christian; Bisi, Nicolo; Torre, Gabriele Dalla; Soliman, Ahmed; Monteiro-Abreu, Nanci; Trushina, Nataliya I.; Krusenbaum, Andrea; Dolouei, Maryam Khodaei; Hellwig, Andrea; Christodoulou, Michael S.; Passarella, Daniele; et al. (Nature Communications, 2024)
Tauopathies such as Alzheimer’s disease are characterized by aggregation and increased phosphorylation of the microtubule-associated protein tau. Tau’s pathological changes are closely linked to neurodegeneration, making tau a prime candidate for intervention. We developed an approach to monitor pathological changes of aggregation-prone human tau in living neurons. We identified 2-phenyloxazole (PHOX) derivatives as putative polypharmacological small molecules that interact with tau and modulate tau kinases. We found that PHOX15 inhibits tau aggregation, restores tau’s physiological microtubule interaction, and reduces tau phosphorylation at disease-relevant sites. Molecular dynamics simulations highlight cryptic channel-like pockets crossing tau protofilaments and suggest that PHOX15 binding reduces the protofilament’s ability to adopt a PHF-like conformation by modifying a key glycine triad. Our data demonstrate that live-cell imaging of a tauopathy model enables screening of compounds that modulate tau-microtubule interaction and allows identification of a promising polypharmacological drug candidate that simultaneously inhibits tau aggregation and reduces tau phosphorylation.